Social media for English language acquisition in Indonesian higher education: Constructivism and connectivism frameworks - Tri Wintolo Apoko; Budi Waluyo (Social Sciences and Humanities Open)
The integration of social media into English language education in Indonesian higher education, though underexplored, holds significant potential to enhance learning experiences within constructivist and connectivist frameworks. This study examined the experiences of 108 EFL undergraduates from both English and non-English departments at a private university in Jakarta, Indonesia. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews. We analysed the data using descriptive statistics and thematic analysis to assess the influence of social media on language learning. The results revealed that undergraduates widely regarded social media platforms such as Instagram, TikTok, Facebook, and WhatsApp as interactive tools that facilitated authentic communication, enhanced both written and spoken English skills, and improved learning strategies, engagement, teaching activities, and academic performance. Despite certain challenges, these platforms offered authentic learning tasks and access to diverse information networks, aligning with constructivist and connectivist principles. The findings highlighted the transformative role of social media as both a supplementary and core educational resource, advocating for its integration into curricula to promote greater student engagement and proficiency in English.